Pengaruh Faktor Eksternal Terhadap Keputusan Hakim: (Studi Kasus di Pengadilan Agama Kisaran) - Lathifa Khairunnisa, Andri Nurwandi, Sabillah Aisyah Futri, Adam Jordan, Ade Safitri, Citra Dwi Sapu (Pusdikra Publishing, 2024)
This research aims to determine the influence of external factors on the judge's decision in a case study civil case at the Kisaran Religious Court. The data source is a judge at the Kisaran Religious Court who is considered representative in providing the required data (a judge who is experienced in resolving civil cases). Data collection was carried out by means of interviews and documentation with the judge. The research results show that the influence of external factors on the judge's decision, if the decision has not been decided by the judge then it could be influenced by the judge's decision, although in fact it should not be influenced and the judge should not be influenced either (judge factors). And the influence of external factors has almost no influence at all on the judge's decision, because it can no longer be questioned or cannot be contested. And if the decision has been decided by the judge and has permanent legal force then it cannot be changed anymore, but if you are not satisfied with the judge's decision then you can submit legal remedies such as, Verzet, Verstek, Appeal, Cassation and also Judicial Review (PK ). And the legal action is carried out by the litigant (internal factors) and not external factors (external factors), because in essence external factors cannot influence a judge's decision, because in theory the judge's decision cannot be contested if the decision has been decided. , unless there is another lawsuit.